2008
DOI: 10.1021/la702550f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Mucin Adsorption

Abstract: The kinetics of adsorption and desorption on a silica-like surface of the large glycoprotein mucin have been measured across a range of temperatures from 25 to 60 degrees C. The area occupied per molecule diminishes with increasing temperature both in the bulk and adsorbed states, implying that the glycoprotein belongs to the "natively open" conformational class. Due to the conformational rearrangement, the specific interaction energy governing desorption greatly increases with temperature, resulting in an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The refractive index increment  at 633 nm in pure water at 25 •C was determined using a Rudolph J357 refractometer as 0.140 ± 0.002 cm 3 /g, in agreement with previous results [31]. Teavigo (97% pure EGCG) was purchased from DSM (Switzerland) and stored under nitrogen.…”
Section: Mucin and Egcgsupporting
confidence: 86%
See 1 more Smart Citation
“…The refractive index increment  at 633 nm in pure water at 25 •C was determined using a Rudolph J357 refractometer as 0.140 ± 0.002 cm 3 /g, in agreement with previous results [31]. Teavigo (97% pure EGCG) was purchased from DSM (Switzerland) and stored under nitrogen.…”
Section: Mucin and Egcgsupporting
confidence: 86%
“…The available area function, , depends not only on M but also on the area a occupied by each adsorbing entity. Previous investigations showed that the adsorption kinetics of pure mucin (i.e., in the absence of EGCG) were consistent with random sequential adsorption (RSA) [31] and the EGCG-mucin complexes do not appear to be qualitatively different in this regard. The form of  appropriate to RSA of disks and spheres was used (equation 42 in ref.…”
Section: Corroboration Of the Adsorption Mechanismmentioning
confidence: 81%
“…The maximum adsorbed amounts ( M max ) are given in Table , which shows that the saturated adsorbed mass increases with concentration. Previously, it was found that Orthana mucin adsorption results in a composite bilayer structure, consisting of an uppermost layer that desorbs rapidly and a layer adjacent to the substrate that desorbs much slower suggesting that the bilayer structure starts to form at 0.1 mg/mL, and up to 10 mg/mL the faster desorbing uppermost layer is small whereas above 20−30 mg/mL this layer becomes relatively thick. Analysis of the TE and TM modes of the optical waveguide enables the extraction of both the film thickness of the adsorbed mucin layer and the total adsorbed mass and it is found that film thickness increases with concentration .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of mucin desorption has been found to follow a double stretched exponential (Kohlrausch) kinetic law: M ( t ) = M max false[ f 1 e −( k 1 t ) normalβ 1 + false( 1 f 1 false) e −( k 2 t ) normalβ 2 false] where M max is the amount of mucin adsorbed at the beginning of desorption, and f 1 , k i , and β i are constants. , Equation was fitted to the data and the fitted parameters for some representative adsorption−desorption curves are given in the Supporting Information. As previously, , the second stretched exponential dominates and we infer a composite structure of the adsorbed mucin layer, with a tightly bound equilibrium layer adjacent to the surface that desorbs slowly; superimposed on this is a structurally distinct second layer with faster rates of desorption. The characteristic desorption times for the slow and fast processes (Table ) are given by false⟨ τ i false⟩ = Γ false( / β i 1 false) / false( β i k i ...…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Considerable attention has been given to understanding the adsorption behavior of mucin and its important functional properties. [14][15][16][17] However, the molecular structure of mucin layers adsorbed onto polymer surfaces has not been sufficiently explored thus far. Little is also known about the conformational changes of mucin that might occur, as is the case for proteins, upon adsorption onto various polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%